BASIC FTBALL and Computer Programming for All. - Vee, Annette (DHQ: Digital Humanities Quarterly, 2023)
In late fall 1965, John Kemeny wrote a 239-line BASIC program called FTBALL***. Along with his colleague Thomas Kurtz and a few work-study students at Dartmouth College, Kemeny had developed the BASIC programming language and Dartmouth Time-Sharing System (DTSS). BASIC and DTSS represented perhaps the earliest successful attempt at computer programming for all, combining English-language vocabulary, simple yet robust instructions, and near-realtime access to a mainframe computer. This article takes a closer look at FTBALL as a crucial program in the history of programming for all while gesturing to the tension between a conception of all and FTBALL's context in an elite, all-male college in the mid-1960s. I put FTBALL in a historical, cultural, gendered context of programming for all as well as the historical context of programming language development, timesharing technology, and the hardware and financial arrangements necessary to support this kind of playful, interactive program in 1965. I begin with a short history of BASIC's early development, compare FTBALL with other early games and sports games, then move into the hardware and technical details that enabled the code before finally reading FTBALL's code in detail. Using methods from critical code studies (Marino 2020), I point to specific innovations of BASIC at the time and outline the program flow of FTBALL. This history and code reading of BASIC FTBALL provides something of interest to computing historians, critical code studies practitioners, and games scholars and aficionados. Annette Vee traces the historical and cultural context of FTBALL as an example of programming for all.